From specificity to sensitivity: affective states modulate visual working memory for emotional expressive faces - Maran, Thomas; Sachse, Pierre; Furtner, Marco (Frontiers in Psychology, 2015)
Previous findings suggest that visual working memory preferentially remembers angry looking faces. However, the meaning of facial actions is construed in relation to context. To date, there are no studies investigating the role of perceiver-based context when processing emotional cues in visual working memory. To explore the influence of affective context on visual working memory for faces, we conducted two experiments using both a visual working memory task for emotionally expressive faces and a mood induction procedure. Affective context was manipulated by unpleasant (Experiment 1) and pleasant (Experiment 2) IAPS pictures in order to induce an affect high in motivational intensity (defensive or appetitive, respectively) compared to a low arousal control condition. Results indicated specifically increased sensitivity of visual working memory for angry looking faces in the neutral condition. Enhanced visual working memory for angry faces was prevented by inducing affects of high motivational intensity. In both experiments, affective states led to a switch from specific enhancement of angry expressions in visual working memory to an equally sensitive representation of all emotional expressions. Our findings demonstrate that emotional expressions are of different behavioral relevance for the receiver depending on the affective context, supporting a functional organization of visual working memory along with flexible resource allocation. In visual working memory, stimulus processing adjusts to situational requirements and transitions from a specifically prioritizing default mode in predictable environments to a sensitive, hypervigilant mode in exposure to emotional events.